Artistic creative social entrepreneurs and business model innovation. Issue 2 (16th December 2019) - Pearse, Noel James; Peterlin, Judita
Abstract : Purpose: From the perspective of role identity theory, the purpose of this paper is to explain how an artistic creative entrepreneur has set up and operates a business that incorporates a component of social responsibility into the business model. Design/methodology/approach: An explanatory case study approach was followed in analysing the case of Alenka Repic, the founder and creative director of the company Kaaita, which operates from Slovenia. Data were collected through documentation and interviews and content analysis was used to analyse the data. Findings: Kaaita has adopted an innovative and socially responsible business model as an artistic creative enterprise. The case study firstly introduces Kaaita and its innovative business model. Thereafter, it describes and discusses the defining roles of Alenka Repic as an entrepreneur and how these roles have shaped what Kaaita does and how it operates. Research limitations/implications: This explanatory case study has presented the unique case of an artistic creative social entrepreneur, and the innovative business model that has been adopted. However, because only one case has been presented here, it is recommended that additional case studies be conducted. It is also recommended that additional research be conducted in the area of sustainable business model innovation. Practical implications: The case illustrates how a more deliberate consideration of their role identity could assist entrepreneurs in aligning their personal values and beliefs with how they create, operate and develop their enterprise. It also serves as a reminder to both scholars and aspiring entrepreneurs that the essence of entrepreneurship is to have the passion and courage to be innovative and disruptive and that educators should focus on cultivating skills that are related to identifying and exploiting opportunities for innovative disruption. Originality/value: The study draws on role identity theory to gain insight into the roles that are exercised in developing an innovative business model that combines diverse types of entrepreneurship.